It's not fair! Students and staff views on the equity of the procedures and outcomes of students' choice of assessment methods. Issue 2 (3rd April 2017) - O'Neill, Geraldine
Abstract : Giving students a choice of assessment methods is one approach to developing an inclusive curriculum. However, both staff and students raise concerns about its fairness, often described as its equity. This study investigates their perceptions of the fairness of the procedures and outcomes of this approach to assessment, in nine modules in a University setting. Using a tool validated as part of the study, students' views on procedural fairness were gathered ( n  = 370 students). In addition, seven module co-ordinators were interviewed. A seven-step approach to the design of the approach was used. The results demonstrated that students were satisfied that their assessment choices were fair in levels of support, feedback, information and, to a lesser extent, student workload and examples of assessment methods. In exploring fairness of the outcomes, the students' grades were not significantly different between the two sets of choices. However, based on staff interviews, the overall grades were higher than previous cohorts and higher than average for current student cohorts in the institution. The discussion highlights some of the complex issues surrounding fairness (equity) using assessment choice and, in addition, the paper refers to some practical tools for its implementation.